Malaysian foreign policy during Mahathir’s administration - Othman, Muhammad Fuad; Othman, Zaheruddin (Medwell Journal, 2013)
Malaysia saw an unprecedented economic achievement during Mahathir’s administration and started taking center stage in the international relations arena during the 1990’s.Malaysia’s profound profile in global and regional relations was largely credited to the robust economic reformation and strengthen inter-governmental relations by Mahathir’s administration, especially with its ties with the ASEAN countries and US/Europe cooperation.This study explains Mahathir’s foreign policy experiences which spans from economic and trade ties to the reinforcement with ASEAN and OIC countries.